2020
DOI: 10.1080/13887890.2020.1788999
|View full text |Cite
|
Sign up to set email alerts
|

New records of polymorphism in Asian libellulid dragonflies (Insecta: Odonata)

Abstract: Polymorphism has rarely been reported from dragonflies of the Libellulidae (Odonata: Anisoptera) family. Here, we report female-limited polymorphism in females of five species of the Libellulidae and a gynandromorph male of Brachythemis contaminata from South Asia. We describe the morphological variation between andromorph and heteromorph females, and collate records of andromorph females from various sources. Yearly number of andromorph females of Crocothemis servilia, Urothemis signata and Neurothemis tullia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(24 reference statements)
1
1
0
Order By: Relevance
“…The high numbers of haplotypes are due to a high degree of cox1 and 16S gene polymorphisms in R. fenestrella samples in Peninsular Malaysia. In fact, the polymorphism that occurred in Odonata were widely reported in other studies [48,49]. Whereas this study showed extremely low haplotype numbers when compared to study done by Jiang et al (2023) [50] on the population of damselfly Ischnura senegalensis (Rambur, 1842) that revealed of 51 haplotype variations.…”
Section: Haplotype Variation and Distribution Of Rhinocypha Fenestrellasupporting
confidence: 46%
“…The high numbers of haplotypes are due to a high degree of cox1 and 16S gene polymorphisms in R. fenestrella samples in Peninsular Malaysia. In fact, the polymorphism that occurred in Odonata were widely reported in other studies [48,49]. Whereas this study showed extremely low haplotype numbers when compared to study done by Jiang et al (2023) [50] on the population of damselfly Ischnura senegalensis (Rambur, 1842) that revealed of 51 haplotype variations.…”
Section: Haplotype Variation and Distribution Of Rhinocypha Fenestrellasupporting
confidence: 46%
“…Gutassociated fungi of dragonfly were highly diverse and discovered as the resource of bioactive compounds (Shao et al, 2015;Lu et al, 2017;Zhang et al, 2020). Crocothemis servilia is one of Asia's most widely distributed dragonfly species, mature males and most females are scarlet-red and yellow, respectively (Joshi et al, 2020). However, no study reported the gut fungal diversity of the dragonfly.…”
mentioning
confidence: 99%